Integrated Materials Management - Carter J. R; Price P (M&E Handbooks, 1993)
This book provides concise and comprehensive coverage of a wide range of subjects in business, finance and law. Preface, Acknowledgements, Control of Physical Resources, Components of a Materials Management System, Materials Planning and Control, Modern Materials Handling, Aspects of Materials Management, Strategic Considerations for Material Management, Physical Distribution Management, Index.